THE IMPORTANCE OF NATURAL NUTRIENTS IN THE DIET OF CATFISH (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article provides information on the categories of fish feeds, predatory fish, non-predatory Fish, benthic Fish, Fish that feed on plankton, Fish that feed on plants, the digestive system of predatory fish, the obesity rate, and rapidly digestible feeds.